Tinjauan Sosial Hukum Islam Terhadap Harta Pejabat Yang Meningkat Dimasa Pandemi Covid-19 - Eril E; Kurniati K; Misbahuddin M; Fadly F (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to find out the social review of Islamic law regarding official assets which increased during the Covid-19 pandemic. This type of research is library research. The approach used is a normative approach (syar'i), which is an approach to a problem that is based on Islamic law originating from the Koran, hadith, ushul fiqh rules, and the opinions of scholars related to the implementation of Islamic law. The results of this study found two possible categories that could occur. First, the assets can be justified if the acquisition is in accordance with the procedures for obtaining assets in accordance with the Shari'a. Second, it can turn into a grave sin if the method of obtaining it falls into the category of procedures that are prohibited in obtaining wealth, such as usury, gifts to officials and seizing government property, corruption or theft and betraying the trust of other people or the people.